Microbial communities associated with benthic faunal assemblages at cold seep sediments of the Sonora Margin, Guaymas Basin - Cruaud, Perrine; Vigneron, Adrien; Pignet, Patricia; Caprais, Jean-Claude; Lesongeur, Françoise; Toffin, Laurent; Godfroy, Anne; Cambon-Bonavita, Marie-Anne (Frontiers in Marine Science, 2015)
The Sonora Margin cold seeps present a seafloor mosaic pattern consisting of different faunal assemblages and microbial mats. To better understand if sedimentary microbial communities reflect this patchy distribution, all major habitats were investigated using four complementary approaches: 16S rRNA 454 pyrosequencing, quantitative polymerase chain reaction, fluorescence in situ hybridization and geochemistry analyses. This study reveals that sediments populated by different surface assemblages show distinct porewater geochemistry features and are associated with distinct microbial communities. In the sediments underlying the microbial mat and the surrounding macrofauna, microbial communities were dominated by anaerobic methane oxidizers (archaeal anaerobic methanotroph ANME) and sulfate-reducing Deltaproteobacteria. In contrast, sediment-associated microbial communities underlying the megafauna habitats (vesicomyids and siboglinids) were characterized by a lower biomass and important proportions of the Marine Benthic Group D (MBG-D), Chloroflexi as well as filamentous Gammaproteobacteria and Deltaproteobacteria. Together, geochemical and microbial surveys indicate that porewater methane concentrations play an important role in the microbial community structure and subsequently in the establishment of the surface colonizers. Furthermore, presence and activity of the surface colonizers influence the underlying microbial communities probably because of modification of energy source availabilities.